Occupational Health and Safety Risk Assessment on Informal Workers in Ogan Ilir, South Sumatra - Adisyah Fitrah Rahmadini; Desheila Andarini; Anita Camelia; Nurmalia Ermi; Mona Lestari (The Indonesian Journal of Occupational Safety and Health, 2021)
Introduction: One of the blacksmith industry centers in South Sumatra is in Limbang Jaya I, Ogan Ilir. Informal businesses such as blacksmiths are businesses that do not have operational standards in their work processes. Various risks from the work process can, therefore, arise, from injury to hearing loss. Therefore, it is necessary to carry out risk analysis in the work of blacksmith sector using Preliminary Hazard Analysis. Methods: This study used a descriptive research method with a qualitative approach through in-depth interviews, hazard checklists, and PHA worksheets. There were 12 informants in this study consisting of 4 key informants and 8 blacksmith worker informants. Results: The results showed that the hazards identified based on the work process were physical hazards, chemical hazards, ergonomic hazards, and psychosocial hazards. The efforts could be made by performing audiometric checks on workers, working time arrangements, stretching before and after work, and the use of Personal Protective Equipment (PPE). Conclusion: Based on the results of risk ranking, it is known that out of 34 lists of hazards that existed in the blacksmith's work process in Limbang Jaya 1 Village, there were 8 types of hazards included in the high risk group, 12 hazards included in the serious risk group, 12 hazards included in the medium risk group, and 2 hazards included in the low risk group.Keywords: blacksmith, preliminary hazard analysis, risk management